ANALISIS PRIORITAS PEMBANGUNAN DAERAH BERDASARKAN PENGARUH REGIONAL, SPESIALISASI DAERAH, DAN KEUNGGULAN KOMPETITIF EKONOMI SEKTORAL DI KABUPATEN ACEH JAYA - Reza Septian Pradana (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
This study aims to identify economic sectors that will be the priority of regional development based on regional influence, regional specialization, and competitive advantage of economic sector in Aceh Jaya Regency. This study uses shift share model analysis and inference analysis by using multiple regression method. The result of estimation by using multiple regression analysis shows that regional specialization variable proxied by Proportionality Shift (PS) score and Competitive Advantage proxied by Differential Shift (DS) score significantly give positive influence to Economics Growth while Regional Influence proxied by Regional Share (RS) insignificantly influents to Economics Growth. The Priority of Regional Development could be foccused on economic sectors which have the high regional specialization and competitive advantage. Based on the result of Shift Share Model analysis, two sectors which have the highest Regional Specialization are Agriculture, Forestry, and Fishing Sector and Construction Sector. Then, two sectors which have the highest Competitive Advantage are Mining and Quarrying Sector and Manufacturing Sector.